Coordination of return-to-work for employees on sick leave due to common mental disorders: facilitators and barriers. Issue 13 (19th June 2022) - Holmlund, Lisa; Hellman, Therese; Engblom, Monika; Kwak, Lydia; Sandman, Lars; Törnkvist, Lena; Björk Brämberg, Elisabeth
Abstract: Purpose: To identify facilitators of and barriers to the coordination of return-to-work between the primary care services, the employee, and the employers from the perspective of coordinators and employees on sick leave due to common mental disorders (CMDs). Material and methods: Descriptive qualitative study. Semi-structured interviews were conducted with eighteen coordinators and nine employees on sick leave due to CMDs. The Consolidated Framework for Implementation Research (CFIR) was used as a starting point for the interview guides and in the thematic analysis of data. Results: The results show facilitators and barriers related to the CFIR domains "intervention characteristics, " "outer setting, " "inner setting, " and "characteristics of individuals." Positive attitudes, an open dialogue in a three-party meeting, and a common ground for the sick leave process at the primary care centre facilitated coordination, while an unclear packaging, conflicts at the employee's workplace, and a lack of team-based work were examples of barriers. Conclusion: The results indicate a need for the detailed packaging of coordination; formalization of coordinators' qualifications and levels of training; and acknowledgement of the role of organizational factors in the implementation of coordination. This is important to further develop and evaluate the efficacy of coordination. IMPLICATIONS FOR REHABILITATION: Positive attitudes to coordination, an open dialogue in a three-party meeting, leadership engagement, routines for the return to work (RTW) process at the primary care centre, and collegial alliances were identified as facilitators. An unclear packaging of the intervention, conflicts at the employee's workplace, lack of team-based work, and lack of coordinator training were identified as barriers. A detailed intervention packaging adapted for the specific setting and formalization of coordinators' qualifications and training is necessary for coordination of RTW. Recognizing organizational factors were identified as being important for the implementation of coordination of RTW for persons on sick leave due to CMDs.